PENINGKATAN KEMAMPUAN DAYA INGAT KATA KERJA BAHASA MANDARIN MELALUI METODE PERAGAAN PADA SISWA KELAS X SMK NEGERI 8 PONTIANAK - Al Vira, Syarifah; Ina, Ina; Veronica, Tjen (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
At this time, Mandarin has been widely studied in various circles, bothchildren and adults. At the education level, Mandarin is also used as acompulsory subject at school. In learning Mandarin there are severalthings that must be mastered by students, such as reading, memorizingvocabulary and using vocabulary in the form of correct Mandarinsentences. However, there are several problems faced by students inlearning Mandarin which are caused by various factors, both internaland external. To improve skills in learning Mandarin, the author usesdemonstration methods in class X SMK 8 Pontianak.To understand the ability of class X students of SMK 8 Pontianak inmastering Chinese vocabulary, the writer uses demonstration methodsto improve students' memory skills in memorizing Chinesevocabulary. The research method used is divided into pre-test andpost-test. This research was conducted from 2 February 2021 to 23March 2021. Based on the pre-test results, it showed that the averagescore was 43.75. After doing research, the average of the post-testshows that the average score is 89.06. This proves that after doing thedemonstration method can improve students' Chinese language skills,can remember Chinese verbs, can also use verbs correctly.